Effects of glucose, glucose metabolites and calcium ions on adenylate cyclase activity in homogenates of mouse pancreatic islets. - Capito, K (1977)
The effects of glucose, a series of glucose metabolites, nicotinamide nucleotides, Ca2+ and p-chloromercuribenzenesulphonate on adenylate cyclase activity in homogenates of mouse pancreatic islets were studied. The basal activity of the adenylate cyclase was approx. 6 pmol of cyclic AMP formed/30 min per microng of DNA at 30 degrees C. The enzyme activity was stimulated by some 150% by fluoride. Starvation of the animals for 48h had no effect on either the basal or the fluoride-stimulated activity. The adenylate cyclase activity was increased by 40-50% when 17 mM-glucose, 10 micronM-phosphoenolpyruvate or 10 micronM-pyruvate was added to the assay medium. The effect of glucose was unchanged in the presence of 17 mM-mannoheptulose, and mannoheptulose alone had no effect. The other glycolytic intermediates, and the coenzymes NAD+, NADH and NADPH, at concentrations up to 1 mM were without any detectable effect on the rate of formation of cyclic AMP. The insulin secretagogue p-chloromercuribenzenesulphonate inhibited the adenylate cyclase markedly even at a concentration of 10 micronM. Calculated concentrations of free Ca2+ of 10 micronM and 0.1 mM inhibited adenylate cyclase by 29 and 71% respectively. It is concluded that both glucose itself and phosphoenolpyruvate and/or pyruvate are true activating ligands for islet and adenylate cyclase and that inhibition of the cyclase by Ca2+ may be of physiological significance.